Understanding Vaccine Hesitancy Among Parents of Children With Autism Spectrum Disorder and Parents of Children With Non-Autism Developmental Delays. (September 2021) - Bonsu, Noël E. Mensah-; Mire, Sarah S.; Sahni, Leila C.; Berry, Leandra N.; Dowell, Lauren R.; Minard, Charles G.; Cunningham, Rachel M.; Boom, Julie A.; Voigt, Robert G.; Goin-Kochel, Robin P.
Parents of children with autism spectrum disorder (ASD) may be at greater risk for developing antivaccine beliefs that lead to vaccine delays and/or refusals for their children. We investigated current parental vaccine hesitancy, parents' beliefs about causes of children's developmental delays, and children's vaccination histories among parents of children with ASD or non-ASD developmental delays. Data were analyzed from 89/511 parents (17.4%) who completed the Parent Attitudes About Childhood Vaccines questionnaire and the Revised Illness Perception Questionnaire; 46.1% had childhood vaccination records available. Overall, 21/89 (23.6%, 95% confidence interval [CI]: 15.0-34.0) of parents were vaccine hesitant (ASD n = 19/21 [90.5%], non-ASD n = 2/21 [9.5%]). Parents of children with ASD were significantly more likely to agree with "toxins in vaccines" as a cause of their child's developmental delays (28.4% vs 5.0%, P = .034). The odds of being vaccine hesitant were 11.9 times (95% CI 2.9-48.0) greater among parents who agreed versus disagreed that toxins in vaccines caused their children's developmental delays. Rates of prior vaccine receipt did not differ between hesitant and nonhesitant groups.